2017
DOI: 10.1002/dneu.22519
|View full text |Cite
|
Sign up to set email alerts
|

To mdivi‐1 or not to mdivi‐1: Is that the question?

Abstract: The fission/division and fusion of mitochondria are fundamental aspects of mitochondrial biology. The balance of fission and fusion sets the length of mitochondria in cells to serve their physiological requirements. The fission of mitochondria is markedly induced in many disease states and in response to cellular injury, resulting in the fragmentation of mitochondria into dysfunctional units. The mechanism that drives fission is dependent on the dynamin related protein 1 (Drp1) GTPase. mdivi-1 is a quinazolino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 54 publications
4
82
1
Order By: Relevance
“…of Mdivi1, off-target effects have been described, including inhibition of K + channels and membrane potential in HL-1 murine atrial cardiomyocytes (370) as well as CI inhibition and modulation of mitochondrial ROS production (34,322). The pros and cons of the use of Mdivi1 as a specific DRP1 inhibitor were recently discussed (368). It was concluded that although the current evidence supports the previously described Mdivi1 bioactivity, use of this molecule requires inclusion of stringent positive controls that directly demonstrate its effect on mitochondrial fission.…”
Section: F Small-molecule Targeting Of Mitochondrial Morphologymentioning
confidence: 99%
“…of Mdivi1, off-target effects have been described, including inhibition of K + channels and membrane potential in HL-1 murine atrial cardiomyocytes (370) as well as CI inhibition and modulation of mitochondrial ROS production (34,322). The pros and cons of the use of Mdivi1 as a specific DRP1 inhibitor were recently discussed (368). It was concluded that although the current evidence supports the previously described Mdivi1 bioactivity, use of this molecule requires inclusion of stringent positive controls that directly demonstrate its effect on mitochondrial fission.…”
Section: F Small-molecule Targeting Of Mitochondrial Morphologymentioning
confidence: 99%
“…As high concentrations of mdivi-1 (50 μM) might have unexpected side effects, 30 Mdivi-1 treatment decreases glutamine oxidation in H460 cells In addition to glucose, glutamine is another major energy source for cancer cells. 43 In the [U-13 C]glutamine tracing assay, glutamine carbons enter the TCA cycle as fully labelled m + 5 α-KG (containing all five carbons from [U-13 C]glutamine tracer).…”
Section: Mdivi-1 Inhibits Oxidative Metabolism In H460 Cellsmentioning
confidence: 99%
“…29 Not surprisingly, mdivi-1 has been widely used as a mitochondrial fusion inducer. 30 Studies showed that mdivi-1 treatment altered mitochondrial morphology and cellular oxygen consumption, induced cell death in cancer cells, and limited tumour size in xenograft models. 4,19 However, a recent study showed that mdivi-1 failed to elongate mitochondria or inhibit recombinant human DRP1 GTPase activity in mouse embryonic fibroblasts (MEFs) and normal neurons, and mdivi-1 reversibly inhibited respiration at mitochondrial complex I to decrease the oxygen consumption rate (OCR).…”
mentioning
confidence: 99%
“…() who reported that Mdivi‐1 is a reversible inhibitor of Complex I and also leads to ROS production. However, a recent commentary from Smith and Gallo () contends that Mdivi‐1 bioactivity may still hold significant promise as a therapeutic agent for manipulating fission, but that further biochemical studies are required to validate the efficacy and specificity in different disease systems and stage of disease progression. The application of Mdivi‐1 for treating heart disease has been explored by several groups (Ong et al, ; Givvimani et al, ; Sharp et al, ).…”
Section: Cryo‐em and Spa Techniques Enter A New Era For Protein Strucmentioning
confidence: 99%